A smile from the past: exploring a fixed bone dental bridge from eighteenth/nineteenth century Porto (Portugal) - Vassallo, Steffi; Esteves, Alexandra Patrícia Lopes; Assis, Sandra; Rodrigues, Zélia; Márquez‐Grant, Nicholas; Malcherek, Anne; Pereira, Manuel F. C.; Chowdhury, Manasij Pal; Alves-Cardoso, Francisca (Wiley, 2026)
This paper presents the first documented case of a fixed bone dental bridge in Portugal. This item was recovered alongside the remains of a young adult individual of indeterminate sex from the 19th century burial site of the 3rd Order of Our Lady of Carmo in Porto, Portugal. Despite the remains being mostly complete and well preserved, the maxilla is edentulous and the mandible is missing, with only two loose mandibular teeth recovered. The cranium, the two lower teeth, cervical vertebrae and dental bridge underwent detailed macroscopic examination with the latter also undergoing macro stereomicroscopy, multiscale x-ray, micro-CT imaging, x-ray diffraction, and ZooMS analyses. The bridge, which measures 24 mm long× 6 mm wide × 12 mm tall, is made from bone and likely sourced from the Bovidae family. It features three rudimentary “teeth” of increasing size with two perforations at each end. Internally, a cuboid-shaped object composed of lead compounds, primarily pyromorphite and cerussite, can be observed on the top right corner. Given its design, overall width, and the loss of the maxillary dentition, it is most likely that the bridge covered the labial surface of the lower right incisors and canine and was secured to the adjacent teeth through wire or thread. However, the possibility of it serving as a prosthetic substitute should not be discounted.
Keywords: 43 History, Heritage and Archaeology; Dental/Oral and Craniofacial Disease; 4301 Archaeology; dental prosthesis; human remains; nondestructive analysis; Portugal; postmedieval